Use of soy as a source of protein in low-fat yogurt production: microbiological, functional and rheological properties (Research, Society and Development, 2020)
The objective of this study was to evaluate the effect of different protein sources incorporated into milk to produce low-fat yogurt (LF-yogurt). Five treatments were used: YC – yogurt control (without protein supplementation), YM – yogurt with milk powder, YWP – yogurt with whey protein, YSP – yogurt with soy protein, and YSF – yogurt with soy flour. Microbiological counts of Streptococcus thermophilus and Lactobacillus bulgaricus, pH, lactic acid and changes in rheological and structural properties (firmness, color, microstructure and syneresis) were followed throughout 28 days of storage. Antioxidant capacity (DPPH and ABTS assay) and total phenolic compounds were also analyzed. Addition of different ingredients influenced S. thermophilus and L. bulgaricus CFU counts. LF-yogurts supplemented with milk powder, soy flour and soy protein were firmest, and yogurts supplemented with milk powder and soy flour had the least syneresis. LF-yogurts with soy flour were darker, redder and yellower, contained more polyphenols and exhibited higher antioxidant activity. Thus, supplementation of LF-yogurt with soy is interesting since it confers functional activity to the yogurt and also modify its technological properties.